If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 53 = -9x Solving 53 = -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 53 + 9x = -9x + 9x Combine like terms: -9x + 9x = 0 53 + 9x = 0 Add '-53' to each side of the equation. 53 + -53 + 9x = 0 + -53 Combine like terms: 53 + -53 = 0 0 + 9x = 0 + -53 9x = 0 + -53 Combine like terms: 0 + -53 = -53 9x = -53 Divide each side by '9'. x = -5.888888889 Simplifying x = -5.888888889
| -9x+9(-4)=-18 | | 12x-10=395 | | 4(n-8)=2 | | 770/55x?=42 | | (2/5)c-12=2 | | 17m+13-5=15m+8+2m | | 4-2=3 | | t-9=2t-3 | | 7x-8+13-5x=-7 | | (6x-13)=140 | | 180=2(4x+1)+5x-4 | | 2.1v=1.68 | | 16x=52.8 | | 3/2k=9/2 | | F(-X)=2(-x)-5 | | 3(n-8)=3n-24 | | 5(-2x-4)=20 | | x-42=-10 | | X-24=28+3x | | 175m-125m+43425=45000-175m | | -8x-9(-19)=11 | | 9/2/9-4/-1/2 | | 16/13p-9p | | -22x-6=39 | | 2x=360-120 | | -5-8+-5j-1-7= | | 4(5+6x)=20 | | 1/4*5/3 | | 2x+55=90 | | 3x+32=25 | | 10x-151=89+2x | | 3(I+1)=5(I-3) |